Skinned - Ramos, Yusnavy, author; Fletcher, Harrison, advisor; Levy, EJ, committee member; Harrow, Del, committee member (Colorado State University. Libraries, 2021)
"Skinned," is a collection of creative nonfiction essays that circle around what it means to love. Through the examination of Psychology findings, color, and masks that take on many forms, the pieces in this collection focus on the narrator's search for a happy ending and delve into experiences that often look and feel like love, but ultimately are not what she seeks. Through a combination of flash nonfiction and longer essays, the collection moves toward renegotiation as the narrator attempts to navigate the world, her family, and the ideas about love that she carries with her, both knowingly and unknowingly.
Keywords: lies; psychology; story; love; disguise; religion